Cytoreductive surgery combined with hyperthermic intraperitoneal chemoperfusion for the treatment of gastric cancer: A single-centre retrospective study. (17th August 2016) - Tu, Yinuo; Tian, Yunhong; Fang, Zhiyuan; ruan, Qiang; Tang, Hongsheng; Zhang, Xiangliang; Wu, Yinbing; Ding, Yan; Cui, Shuzhong
Abstract: Aim: Cytoreductive surgery (CRS) combined with hyperthermic intraperitoneal chemoperfusion (HIPEC) is the treatment regime most likely to achieve prolonged survival in patients with peritoneal carcinomatosis from gastroenteric cancer. To date, few publications have focused on the treatment of patients with gastric cancer alone. Several controversies remain unsolved, including the safety and effectiveness of the CRS–HIPEC combination regime, particularly in cases where HIPEC is used as adjuvant treatment after CRS. Therefore, in the current study, we aimed to evaluate the safety and effectiveness of CRS combined with HIPEC in patients with gastric cancer. Method: Data from 231 patients with a median age of 55.1 years treated with the CRS–HIPEC combination regime between January 2009 and December 2014 were retrospectively reviewed. All patients underwent the combination therapy (mean of 2.4 cycles per patient, range, 1 to 4 cycles). Results: Median overall survival was 37.0 months, with 1-, 2- and 3-year survival rates recorded as 83.4%, 68.5%, and 38.7%, respectively. The serum levels of carcinoembryonic antigen (CEA) and carbohydrate antigen 199 (CA199) were significantly decreased after combination therapy in the completeness of cytoreduction (CCR)-0 and CCR-1 groups, while no significant changes observed in marker levels were observed in the CC ≥2 group. The post-operative morbidity and mortality rates were 6.9% and 0.9%, respectively. Multivariate analysis revealed low TNM tumour stage, ascites condition and CCR score as independent predictors for better survival. Conclusion: In view of the acceptable morbidity and mortality rates we propose that CRS combined with HIPEC presents an effective and safe treatment modality for patients with gastric cancer, especially in cases where optimal cytoreduction is achieved before the HIPEC procedure.